Effect of sports experiences on competition level and exercise habits in Japanese collegiate athletes - Kohmura, Y.; Suzuki, K.; Someya, Y.; Yamazaki, K.; Aoki, K. (Journal of Human Sport & Exercise, 2023)
In this study, we investigated the athletic experiences of former collegiate Japanese athletes and compared their competitive results and current exercise habits. A questionnaire survey was completed by physical education or health and sports science students via mail. We sent the survey to 9,507 people; 2,141 questionnaires were returned, accounting for a recovery rate of 22.5%. We collected data on the current level of physical activity, history of sports experiences, and type of athletic competitions participated in from childhood until adulthood. An analysis was conducted on 1,999 participants. The results suggested that Japanese collegiate athletes had continued the same sport since elementary school. Conversely, several recent athletes had multiple-sport experiences and had started sports from an early age. There were no differences in athletic history and athletic performance between some age groups. We believe that having experience in a variety of sports has no adverse effect on athletic performance or exercise habits. In conclusion, compared to the past, the number of collegiate athletes with multiple experiences has increased. However, their experience differed from multiple-sport environments observed outside Japan. It is necessary to reconsider the sports environment of Japanese children in the future.